Faktor-Faktor yang Berpengaruh terhadap Dividen Payout Ratio - Putri, Yulia Isnaini; Samrotun, Yuli Chomsatu; Dewi, Riana R (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2021)
This study aims to examine and analyze the factors that influence the dividend payout ratio in manufacturing companies in various industry sectors and the basic & chemical industry sector. The population of this research is 17 manufacturing companies in various industry sectors which are listed on the Indonesia Stock Exchange in the period of 2016-2018. With a total sample of 51 and this sampling technique uses a purposive sampling method. Testing the hypothesis of this study using multiple linear regression. The independent variables in this study are profitability (ROA), liquidity (CR), leverage (DER) and earnings per share (EPS). Whereas the dependent variable is the dividend payout ratio (DPR). The results of this study indicate that profitability (ROA), liquidity (CR) and earnings per share (EPS) affect the dividend payout ratio, laverage (DER) does not affect the dividend payout ratio.